Vulvar lichen sclerosus in girls and adult females: A single‐center retrospective study of 744 patients in China - Liu, Lin; He, Yuexi; Hu, Qiang; Sun, Kailv; Yang, Min; Chang, Jianmin (Journal of dermatology, 2024)
Vulvar lichen sclerosus (VLS) is a chronic, inflammatory disease which is accompanied by itching and pain, affecting the patient's daily life and sexual activity. However, the disease characteristics of children and adults are not completely the same. Currently, there are few studies in China that compare the characteristics of VLS between girls and adult female patients. The aim of this study was to compare the epidemiology, clinical features, and combined autoimmune diseases of VLS patients between girls and adult females, and to help clinicians better understand VLS in different age groups. We enrolled 744 female patients for analysis, divided by age into a child group (<18 years) and an adult group (≥18 years). Among girl patients, 94.6% had preadolescent onset, while among adult female patients, only 4.6% had preadolescent onset, which was a statistically significant difference. The highest percentage of adult female patients had onset during their child‐bearing period (75.4%), while 20% had postmenopausal onset, with a significant difference when the three onset states were compared. White patches were equally common in both girl and adult female patients' external genital area, while mossy lesions and labia minora atrophy were more common in adult female patients. Involvement of the clitoris, labia minora, and vaginal opening area were more common in adult patients. The perianal area was more commonly involved in girl patients. We found eight cases (1.2%) of secondary squamous cell carcinoma in adult female patients. We also found that 13 patients had concurrent lichen sclerosus lesions on the vulva and extragenital region, including two girls and 11 adult females. Extragenital lichen sclerosus (EGLS) occurred mostly in the torso. Clinicians should be aware of these differences so that early diagnosis and treatment of the disease can be achieved, to avoid irreversible anatomical alterations and the risk of cancer.